SEDIMENT TRANSPORT IN THE BASIN OF PULAU BAAI PORT, BENGKULU - Mihardja, D. K.; Supiyati, -; Suprijo, T. (Marine Research in Indonesia, 2007)
The 2D horizontal model has been simulated to investigate a sedimentation and erosion pattern in the basin of Pulau Baai port ? Bengkulu Sumatera. The model was verified with observed data from the Indonesian Research Center for Marine Geology (Arifin et al., 2001). The simulation results of the hydrodynamic model shows a good agreement with the observed data. In -regard to the elevation of sea level, the difference between simulation and the observed data is about 4.6 cm, giving averaged error of about 2.93 %, and the difference in velocity is 6.8 cm/s or in the order of error of about 20.1 %. The results of the model on sediment transport qualitatively show comparable values to the observed ones, although in some parts of the area, the model is still to be adjusted. Simulation results show that the strong current occurs in the harbor channel during the time of spring flood tide with a speed of about 95.4 cm/s, while the ebb current is 54.1 cm/s. The results of the model on sediment transport show that the erosion area occurs in the northeastern part of the basin and sedimentation takes place in the southwestern to southeastern of the channel. The channel port is generally eroded, and sedimentation occurs in the mouth and the western part of offshoreward of the channel, and erosion is identified in the eastern part of the offshoreward of the channel.